Unusual microbial mat‐related structural diversity 2.1 billion years ago and implications for the Francevillian biota. Issue 5 (20th June 2018) - Aubineau, Jérémie; El Albani, Abderrazak; Chi Fru, Ernest; Gingras, Murray; Batonneau, Yann; Buatois, Luis A.; Geffroy, Claude; Labanowski, Jérôme; Laforest, Claude; Lemée, Laurent; Mángano, Maria G.; Meunier, Alain; et al.
Abstract: The 2.1‐billion‐year‐old (Ga) Francevillian series in Gabon hosts some of the oldest reported macroscopic fossils of various sizes and shapes, stimulating new debates on the origin, evolution and organization of early complex life. Here, we document ten representative types of exceptionally well‐preserved mat‐related structures, comprising "elephant‐skin" textures, putative macro‐tufted microbial mats, domal buildups, flat pyritized structures, discoidal microbial colonies, horizontal mat growth patterns, wrinkle structures, "kinneyia" structures, linear patterns and nodule‐like structures. A combination of petrographic analyses, scanning electron microscopy, Raman spectroscopy and organic elemental analyses of carbon‐rich laminae and microtexture, indicate a biological origin for these structures. The observed microtextures encompass oriented grains, floating silt‐sized quartz grains, concentrated heavy minerals, randomly oriented clays, wavy‐crinkly laminae and pyritized structures. Based on comparisons with modern analogues, as well as an average δ 13 C organic matter (Corg ) composition of −32.94 ± 1.17‰ (1 standard deviation, SD ) with an outlier of −41.26‰, we argue that the mat‐related structures contain relicts of multiple carbon pathways including heterotrophic recycling of photosynthetically derived Corg . Moreover, the relatively close association of the macroscopic fossil assemblages to the microbial mats may imply that microbial communities acted as potential benthic O2 oases linked to oxyphototrophic cyanobacterial mats and grazing grounds. In addition, the mat's presence likely improved the preservation of the oldest large colonial organisms, as they are known to strongly biostabilize sediments. Our findings highlight the oldest community assemblage of microscopic and macroscopic biota in the aftermath of the "Great Oxidation Event, " widening our understanding of biological organization during Earth's middle age.